Postburn Abdominal Pain of Gastrointestinal Origin: A Scoping Review - Amjad Soltany, MD; Munawar Hraib, MD; Shant Apelian, MD; Alin Mallouhy, MD; Edwar Kounsselie, MD; Souliman Diab, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. After burn injury, patients may have abdominal pain due to several causes and etiologies, some of which could be life-threatening, including pancreatitis, stress ulcers, Clostridium difficile infection, and so forth. This pain sometimes poses a major diagnostic challenge. This scoping review is the first reported review to address and discuss this entity of patients after burn injury in abdominal pain of gastrointestinal origin. A scoping review of PubMed, Google Scholar, and other electronic research sites was performed. All relevant articles of any study design were included in this review. Variables included in this study were sex distribution, age, related total burn surface area, incidence rate, characteristics of pain, diagnosis, management, outcomes, and mortality rate. The medical literature identified 114 articles. According to our inclusion criteria, 91 articles were reviewed in this article. Through these articles, we reviewed in detail the characteristics of postburn abdominal pain, the relevant diseases responsible for this complaint, the epidemiologic features of these diseases, and potential management approaches aiming to help burn specialists in making earlier diagnosis and, thus, timely treatment. Early recognition of postburn abdominal pain, as well as timely diagnosis and treatment, play a significant role in prognosis and mortality. Thus, it is extremely important for burn specialists and plastic surgeons to thoroughly investigate postburn abdominal pain. Also, one of the aims of this review was to shed light on the important role of the multidisciplinary team in burn patient management to improve the prognosis.